Analisis Ekonomi Usahatani Lada di Desa Kondoano Kecamatan Mowila Kabupaten Konawe Selatan - Wulandari, Gusti Ayu; Bahari, Bahari; Sadimantara, Fahria Nadiriati (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2019)
This study aims to determine the condition of pepper farming and the economic feasibility of pepper farming in Kondoano Village, Mowila Subdistrict, Konawe Selatan District by analyzing income between revenues and costs. Determination of the study area was carried out intentionally (purposive) and sampling was done by simple random sampling which was used to obtain 33 pepper farmers. Data were analyzed using R/C ratio data analysis. The average total income of pepper farming in Kondoano Village, Mowila Subdistrict, South Konawe Regency is IDR 4,265,813/planting season with a total cost of IDR 22,118,063 with an acceptance rate of IDR 26,383,875. The economic feasibility of pepper farming in Kondoano Village, Mowila Subdistrict, Konawe Selatan Regency shows that the yield of the R/C ratio of pepper farming is 1.19, which is greater than 1. This indicates that pepper farming is feasible and can be continued.